Adsorption of n-Aliphatic Alcohols in the Determination of Surface Areas of Metal-Doped Alumina Samples - A.K. Khattak; M. Afzal; M. Saleem; G. Yasmeen; J. Afzal (Adsorption Science & Technology)
A series of metal-impregnated alumina samples were prepared by the incipient wetness impregnation technique. The surface areas of the powdered samples (A L and A BET ) were determined by the two most common methods, i.e. the Langmuir method and the BET method. The adsorbates used were methanol, ethanol, l-propanol and n-butanol (n-aliphatic alcohols) which were designated C 1 , C 2 , C 3 and C 4 , respectively. It was observed that A L and A BET of the adsorbent occupied by the adsorbate molecules decreased from C 1 to C 4 . It was also noted that the variation of A L and A BET with temperature followed exactly the same trend.